A NOVEL APPROACH: LEVERAGING A GENERAL THEORY OF APPLIED ALGORITHMS FOR HIGH-LEVEL LANGUAGE DESIGN - Колісник, Валерій; Бодик, Остап (Modern engineering and innovative technologies, 2025)
The software development industry has long recognized the need for an efficient theory to propel progress in programming technology. Despite continuous efforts, attaining a comprehensive theory has proven to be a formidable challenge. The study introduces